Relationship Quality Between Customer and Provider in the Service Sector - Alwie, Aryaty (2008)
The relationship quality can be used to assess the effectiveness of relationship marketing (Hennig-Thurau, et aI., 2002). By adopting Nordic approach, relationship quality in this study consists of two levels of interaction, i.e. interpersonal and organizational levels. In addition, since the relationship quality is not tied down to any standardized dimension, the study aims to investigate the dimensions of relationship quality in services sector, using two types of services, i.e. credence and experience services. The data was collected using personal interview on the selected residents of Putrajaya. For this purpose, two sets of questionnaire were developed for the two services studied (credence & experience services). The study gathered 421 completed questionnaires. The data were then analyzed using factor analysis, multiple regression and discriminant analysis to fulfill the research objectives. The findings showed that both levels were empirically important for service sector. However, the findings tend to differ slightly according to the type of service. At interpersonal level, closeness factor was significant for credence services but not for experience services. Communication and special care were significant for both service types, whereas a new dimension (communication quality), that emerged from the study, was not significant for both service types. At organizational level, trust was significant for experience services but not for credence services. Nonetheless, commitment and satisfaction showed significant findings for both service types. Based on the study, it is recommended that credence service firms can exploit 'closeness' through friendliness, trustworthiness, responsiveness, competency, and empathy in service to build relationship with customers. Contrary to that of credence service firms, experience service firms might focus on developing customers trust on the organization by delivering highly skilled services along with strong support from the organization.